Demographic Variables and Library Patronage of Undergraduate Students at Universities in South West Nigeria - Tella, Adeyinka; Odunola, Akanmu Oluwole (Mousaion: South African Journal of Information Studies, 2021)
This study investigated the influence of demographic variables, such as gender, age, and the levels of study, on the library patronage by the undergraduate students at universities in South West Nigeria. It also focused on the improvements and innovations wanted by the undergraduate students in the library in view of the technological advancements ushered in by the fourth industrial revolution, and the hindrances to the patronage of the library. A survey research design was adopted using a sample size of 1 333 respondents selected out of the total population of 239 048 undergraduate students at universities in South West Nigeria. A questionnaire was used to collect the data, which were analysed using frequencies, percentages, mean and standard deviation, Pearson’s chi-squared test and regression. The study found that the demographic variables have a significant influence on the library patronage. The most important improvements and innovations wanted by the respondents included high speed internet facilities, the introduction of artificial intelligence and robotics, increased subscriptions to more databases such as Scopus and Web of Science, and stocking the library with recent information materials that comprise both print and electronic materials. Hindrances and factors that discourage library patronage are limited and non-functioning workstations, poor networks and outdated collections. The study recommended that Nigerian university libraries provide high speed internet facilities, introduce artificial intelligence and robotics to the operations and services of the libraries, increase their academic subscriptions, and stock the libraries with recent collections.